2015
DOI: 10.1039/c4ta05445h
|View full text |Cite
|
Sign up to set email alerts
|

The role of conjugated side chains in high performance photovoltaic polymers

Abstract: Four new D–A type copolymers, namely, PBDT-DFQX-PP, PBDT-DFQX-TP, PBDT-DFQX-PT and PBDT-DFQX-TT, were designed and synthesized to investigate the influence of conjugated side chain pattern on photovoltaic properties of conjugated polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…The other high‐energy band at 400–450 nm and the low‐energy band located at 450–700 nm correspond to the characteristic dual‐band of the D‐A system, which are attributed to localized π–π* transitions in the polymeric backbone and the intracharge transfer (ICT) transition between the BDTOT donor and the FBT or BT acceptor moiety, respectively. Similar results have also been observed in other D‐A copolymers based on BDT and FBT or BT with conjugated side chains . Notably, introducing F atoms on the polymer backbone makes the λ max of the polymers blue‐shifted, that is, λ max value (543 nm) of ICT for PBDTOT‐FBT is 40 nm blueshifted from that of PBDTOT‐BT (583 nm).…”
Section: Resultssupporting
confidence: 84%
“…The other high‐energy band at 400–450 nm and the low‐energy band located at 450–700 nm correspond to the characteristic dual‐band of the D‐A system, which are attributed to localized π–π* transitions in the polymeric backbone and the intracharge transfer (ICT) transition between the BDTOT donor and the FBT or BT acceptor moiety, respectively. Similar results have also been observed in other D‐A copolymers based on BDT and FBT or BT with conjugated side chains . Notably, introducing F atoms on the polymer backbone makes the λ max of the polymers blue‐shifted, that is, λ max value (543 nm) of ICT for PBDTOT‐FBT is 40 nm blueshifted from that of PBDTOT‐BT (583 nm).…”
Section: Resultssupporting
confidence: 84%
“…Interestingly, the two copolymers containing alkylthienyl side chains, TQxBT and TQxFBT , showed intense absorption in the 300–500 nm range and a slightly redshifted maximum absorption peak, compared to the polymers PQxBT and PQxFBT substituted with phenyl side chains. This difference could arise from the characteristic intramolecular interactions between the more electron‐donating thienyl moieties and the Qx unit …”
Section: Resultsmentioning
confidence: 99%
“…The side chains flanking on the two‐dimensional (2D) conjugated unit BDT, such as phenyl substituted BDT (BDTP) and thienyl substituted (BDTT), play an critical role not only in the solubility for polymer but also in their optical and electrical properties . Compared with the two building blocks, the weaker electron‐donating nature of BDTP has relatively lower HOMO energy levels, which has been used to effectively lower the polymer energy levels than thienyl substituted BDTT unit . For example, Li et al reported an efficient ITIC‐based PSC with a wide bandgap polymer donor of J52.…”
Section: Introductionmentioning
confidence: 99%